The impact of competition on financial performance of SMEs”: a case of Vineyard Funeral Assurance - Phiri, Dagny (Midlands State University, 2017)
The purpose of this study was to establish the impact of competition of financial performance of Small and Medium Enterprises in the Funeral Assurance sector in Zimbabwe. The SMEs in Zimbabwe have undergone tremendous growth over the last four years. Despite the undeniable effects of competition on their financial performance which is unavoidable since there is rapid increase on globalisation, technology and entry of new firms into the industry. The descriptive research approach was used to carry out this study. The population of the study was from management and staff of Vineyard Funeral Assurance which was the case company. Stratified random sampling was employed on this study to select a sample of 24(69%).The study used both primary data from questionnaire administration and secondary data from IPEC quarterly reports for the periods 2013 -2016.Regression analysis using strata 11 statistical package was used to analyse the relationship between competition and financial performance. Qualitative data was analysed using graphs, tables and charts and mode as a measure of central tendency was employed. The independent variable was competition (entry of new firms, introduction of new products by competitors, expansion of competitor’s business horizons and increase in advertising costs) while dependent variable was SMEs financial performance(sales, costs, profitability).The results from both findings(quantitative and qualitative) indicated that competition has a negative effect on financial performance of SMEs. The study recommended that SMEs should adopt competitive strategies for them to remain relevant in competitive business environments.